STUKTUR KOMUNITAS PADANG LAMUN DI SEKITAR DESA TOSEHO KECAMATAN OBA KOTA TIDORE KEPULAUAN - Anisa Irwan; Calvyn F. A. Sondak; Sandra O. Tilaar; Esther D. A. Angkouw; Agung B. Windarto; Billy Th. Wagey (Sam Ratulangi University, 2023)
Seagrasses are flowering plants that are fully adapted to being immersed in seawater. Seagrass plants consist of rhizomes, leaves and roots. This study aims to identify the types of seagrasses and determine the structure of seagrass community. This research was conducted in July 2023 around Toseho Village, Oba Subdistrict, Tidore City Kepulaun with coordinate points on transect 1 which is 0°21'20.72